2013
DOI: 10.1007/s13277-013-1159-3
|View full text |Cite
|
Sign up to set email alerts
|

Notch-1-mediated esophageal carcinoma EC-9706 cell invasion and metastasis by inducing epithelial–mesenchymal transition through Snail

Abstract: Notch has recently been shown to promote epithelial-to-mesenchymal transition (EMT) by involving in the EMT process that occurs during tumor progression and converts polarized epithelial cells into motile, invasive cells. However, it is still unclear whether the Notch signaling pathway is associated with the regulation of EMT in esophageal carcinoma. The present study explored Notch-1-mediated esophageal carcinoma EC-9706 cell invasion and metastasis by inducing epithelial–mesenchymal transition through Snail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Notch-1 has been implicated in tumor metastasis in a variety of cancer types [ 14 ]. We investigated whether Notch-1 downregulation influenced the migratory capacity of salivary adenoid cystic carcinoma cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch-1 has been implicated in tumor metastasis in a variety of cancer types [ 14 ]. We investigated whether Notch-1 downregulation influenced the migratory capacity of salivary adenoid cystic carcinoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Notch-1 was shown to promote the invasion and metastasis of esophageal carcinoma cells by inducing epithelial-mesenchymal transition (EMT) [ 14 ]. Activation of Notch-1 signaling was demonstrated in gefitinib-resistant lung cancer cells undergoing EMT [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that Jagged1-induced Notch signaling activation induces EMT through Slug-mediated repression of E-cadherin [ 35 ]. A recent study has shown that Notch1 mediates esophageal carcinoma cell invasion and metastasis by inducing EMT through upregulation of Snail [ 38 ]. Likewise, our study showed that the EMT process was closely related to Notch1 signaling in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH1 expression was associated with cell aggressiveness and 5-FU drug resistance in ESCC patients [125]. NOTCH1 increased invasion and metastasis of ESCC cell line EC-9706 through EMT transducted by Snail [126]. High NOTCH1 protein expression was related to poor survival in ESCC [127].…”
Section: Introductionmentioning
confidence: 99%